Antiapoptotic factor humanin is expressed in normal and tumoral pituitary cells and protects them from TNF-α-induced apoptosis - Gottardo, María Florencia (2014)
Humanin (HN) is a 24-amino acid peptide with cytoprotective action in several cell types such as neurons and testicular germ cells. Rattin (HNr), a homologous peptide of HN expressed in several adult rat tissues, also has antiapoptotic action. In the present work, we demonstrated by immunocytochemical analysis and flow cytometry the expression of HNr in the anterior pituitary of female and male adult rats as well as in pituitary tumor GH3 cells. HNr was localized in lactotropes and somatotropes. The expression of HNr was lower in females than in males, and was inhibited by estrogens in pituitary cells from both ovariectomized female and orquidectomized male rats. However, the expression of HNr in pituitary tumor cells was not regulated by estrogens. We also evaluated HN action on the proapoptotic effect of TNF-α in anterior pituitary cells assessed by the TUNEL method. HN (5 µM) per se did not modify basal apoptosis of anterior pituitary cells but completely blocked the proapoptotic effect of TNF-α in total anterior pituitary cells, lactotropes and somatotropes from both female and male rats. Also, HN inhibited the apoptotic effect of TNF-α on pituitary tumor cells. In summary, our results demonstrate that HNr is present in the anterior pituitary gland, its expression showing sexual dimorphism, which suggests that gonadal steroids may be involved in the regulation of HNr expression in this gland. Antiapoptotic action of HN in anterior pituitary cells suggests that this peptide could be involved in the homeostasis of this gland. HNr is present and functional in GH3 cells, but it lacks regulation by estrogens, suggesting that HN could participate in the pathogenesis of pituitary tumors.